PARTICIPATION OF WOMEN IN SHAPING INTERNATIONAL LAW: A MANISFESTATION OF WOMEN CIVIL AND POLITICAL RIGHTS - Zunnuraeni Zunnuraeni; Erlies Septiana Nurbani; Aisyah Wardatul Jannah (Fakultas Hukum, Universitas Diponegoro, 2023)
This article discusses about the participation of women in the creation of international human rights law through international conventions and court decisions. It evaluates whether existing international instruments effectively ensure equality between men and women in civil and political rights. This is a qualitative research with historical and conceptual approaches. This research reveals that woman involvement remains limited due to gender bias and male-dominated norms. This male dominance has resulted in human rights rules that provide formal equality but fail to significantly impact the substantive fulfillment of women's civil and political rights. This needs transformation towards gender-responsive international law, emphasizing the need for reformulation and reinterpretation of international norms, greater inclusion of women as state delegates in the law-making process, and achieving gender parity in international courts. This transformation is essential for ensuring that international law genuinely reflects and addresses the social and economic conditions of women, moving beyond mere formal equality to substantive equality. It is in need a more inclusive and effective approach to international law that truly embodies gender equality in civil and political rights.